Ag Nanowire-Based Conductive Textiles for Electronic Devices: An Introductory Review - Choi, Chunghyeon; Lim, Sooman; Gwang Yun, Tae; Marinkovic, Dragan; Matteini, Paolo; Hwang, Byungil (Nano, 2024)
Conductive textiles (c-textiles) allow a significant advancement in wearable technology, offering new opportunities for mobile devices. Silver nanowires (AgNWs) with exceptional electrical conductivity, flexibility, and stretchability have been studied as the most promising conductive materials to provide electrical conductivities to insulating textiles. In this paper, an overview of the recent advancements in the synthesis and application of AgNWs and their integration into textile materials are discussed, highlighting their applications to various electronic devices. The diverse applications of AgNWs to transparent conducting electrodes; and multifunctional fabrics capable of sensing, heating, and providing electromagnetic interference shielding are introduced underscoring the versatility and potential of AgNW-based textiles. Based on the overview, challenges of AgNW-based c-textiles including low durability and difficult scalability of production processes are discussed which help readers to understand the future direction of the research of AgNW-based c-textiles.
Keywords: Ag nanowires; Conductive; Conductive textiles; Diverse applications; Electrical conductivity; Electromagnetic interference shielding; Electronics devices; Silver nanowires; Textile materials; Transparent conducting electrodes; conductive; electronics; Silver nanowire; textile